Propostas metodológicas para o ensino de filosofia no ensino médio: análise à luz de ideias de Alejandro Cerletti - Santos, Rodrigo Barboza dos (2015)
This thesis presents the results of a bibliographic nature of investigation from the following problem: what aspects pointed out by Alejandro Cerletti in the work O ensino de filosofia como problema filosófico as inherent in the teaching of philosophy in high school, are made in the two methodological proposals offered to high school teachers in Brazil contained in the works: Filosofia em sala de aula: Teoria e prática para o ensino médio de Lídia Maria Rodrigo (Campinas, SP. Autores Associados, 2009) and Metodologia do ensino de filosofia: uma didática para o ensino médio de Sílvio Gallo (Campinas, SP. Papirus, 2012)? The hypothesis which broke was that some important elements of thinking Cerletti would be present in two works analyzed. This hypothesis was somehow proven as shown in this paper also points out some differences. Have been met, too, initially thought objectives: to clarify the concept of Alejandro Cerletti philosophy teaching as a philosophical problem, identify and point to the presence of elements of design Cerletti, as well as differences and peculiarities in the works of Rodrigo and Gallo and offer indications from the analyzes as a contribution to discussions about philosophy of education in high school.